Flows and Practices: Integrated Water Resources Management (IWRM) in African Contexts. (February 2014) - Mehta, Lyla; Movik, Synne
Summary: For the past two decades, Integrated Water Resources Management (IWRM) has been considered the dominant paradigm in water resources. It is the flagship project of supranational global bodies such as the Global Water Partnership (GWP) and has also been actively promoted by multilateral and regional development banks (e.g. the World Bank; African Development Bank) as well as bilateral donor agencies which make it out to be the panacea to address the water management crisis in the global south, leading to major water reforms programmes and the rewriting of national policies drawing on IWRM principles in a range of countries in southern Africa. This paper offers a conceptual approach for studying the evolution, spread and uptake of IWRM. It then turns to the actual practices, and how IWRM has been interpreted in multiple ways, and how it aligns with existing patterns of legal pluralism. The paper proposes a conceptual framework that builds on three main themes, the flow of IWRM as an idea in international and national fora, the translation and adoption of IWRM into national contexts, and the practice of IWRM in local contexts. In constructing such a conceptual framework, we draw on several strands of thought, including policy discourse, network and regime theory ( flows ), translation theory and donor‐recipient studies ( translation and adoption ) and theories of legal pluralism, institutional bricolage and agency ( practices ). With this framework we hope it will be possible to trace the spread, transformation and uptake of IWRM across global, national and local scales, to unearth the convergences and divergences in understandings and applications of the notion of IWRM raising challenges and issues for debate and further research and key actors operating at different levels mediating/moderating/articulating the travel of policy ideas. The latter may create generic insights on policy processes and practice that goes beyond the concept of IWRM and the water world. This framework will guide the critical study of various interpretations and challenges of how policy ideas travel at multiple political and geographical scales, from macro political forums to localised arenas and communities, speaking to wider themes such as policy translation and uptake and the politics of the development process.